2019
DOI: 10.1038/s41598-019-53852-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and label-free biosensor for the detection of Plasmodium falciparum histidine-rich protein II in saliva

Abstract: Malaria elimination is a global public health priority. To fulfil the demands of elimination diagnostics, we have developed an interdigitated electrode sensor platform targeting the Plasmodium falciparum Histidine Rich Protein 2 (PfHRP2) protein in saliva samples. A protocol for frequency-specific PfHRP2 detection in phosphate buffered saline was developed, yielding a sensitivity of 2.5 pg/mL based on change in impedance magnitude of the sensor. This protocol was adapted and optimized for use in saliva with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Ideally, such challenges and limitations can potentially be overcome with properly designed biosensors, that must fill the gap of high sensitivity and specificity, as well as being easily miniaturized for point-of-care diagnosis. Although there are several reports of biosensors for malaria diagnosis, these are mainly based on the use of enzymes as a target [ 11 , 16 , 17 , 52 , 53 , 54 ], i.e., RDTs. Nevertheless, as mentioned above, these have been threatened by parasite genetic evolution, and they do not detect low-parasitemia (100 parasites/µL of blood far from the ideal less than 5 parasites/µL of blood) or quantify infection.…”
Section: Biosensors For Hemozoin-based Malaria Diagnosismentioning
confidence: 99%
“…Ideally, such challenges and limitations can potentially be overcome with properly designed biosensors, that must fill the gap of high sensitivity and specificity, as well as being easily miniaturized for point-of-care diagnosis. Although there are several reports of biosensors for malaria diagnosis, these are mainly based on the use of enzymes as a target [ 11 , 16 , 17 , 52 , 53 , 54 ], i.e., RDTs. Nevertheless, as mentioned above, these have been threatened by parasite genetic evolution, and they do not detect low-parasitemia (100 parasites/µL of blood far from the ideal less than 5 parasites/µL of blood) or quantify infection.…”
Section: Biosensors For Hemozoin-based Malaria Diagnosismentioning
confidence: 99%
“…In healthcare, a great deal of biosensors have been developed to detect pathogens and cancers, as well as to measure glucose and oxygen levels. Impedimetric biosensors gain traction in diagnostic purposes due to their high sensitivity, low cost and miniaturization capability [ 64 ]. For malaria diagnosis, various types of immunosensors for detection of Pf HRP2 were fabricated on the basis of direct or sandwich immunoassays, with detection limit as low as 10 fg/mL in spiked plasma and 18 fg/mL in spiked whole blood [ 65 ].…”
Section: Antigen-based Diagnostic Methodsmentioning
confidence: 99%
“…As a non-destructive technique, EIS was used to monitor all the stages involved and it enabled rapid detection of the disease. Indeed the work done by Soraya et al [ 76 ] reported the development of an ultrasensitive and label free sensor for histidine-rich protein 2 produced by the malaria parasite Plasmodium falciparum (fpHRP2) and the sensor showed enough potential to be developed into a POC diagnostic device for eliminating malaria. The impedance sensor demonstrated the use of an interdigitated electrode sensor surface for immobilizing the capture probe anti- fpHRP2 monoclonal antibodies.…”
Section: Review Of Recent Electrochemical Biosensors For Eids and Re-mentioning
confidence: 99%